The Effect of Visualization Learning and Practice on Freestyle Swimming Speed in Children Aged 10-13 Years - Bagaskoro, Ki Priyo; Tarigan, Herman; Kurniawan, Candra; Nurseto, Fransiskus (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
The aim of this research is to determine the effect of visualization and practice learning on freestyle swimming speed in children aged 10–13 years at the Ben Swimming Course. The method used is experimental with the sample used was 30 children,. The instrument used was a 25-meter freestyle swimming speed test. The data analysis technique uses tests and measurements, namely t test analysis with α = 0.05, through prerequisite tests, normality tests, and homogeneity tests. Based on the results of the research that has been carried out, a conclusion can be drawn that: 1) There is a significant influence of visualization learning and practice on freestyle swimming speed, with a value of tcount = 13.153 > ttable = 2.145. 2) There is no significant effect of the control group on freestyle swimming speed, with a value of t = 1.743 < ttable = 2.145. 3) There is a significant difference between the visualization and practice learning group and the control group regarding freestyle swimming speed, with a value of t = 2,100 > t table = 2,048.